Pengaruh Kualitas Produk dan Lokasi Terhadap Keputusan Pembelian di Keripik CV Cita Mandiri Batu - Dania Khriesma Devy; Joko Samboro (INDO PUBLISHING, 2025)
Product quality and location are important factors that influence consumer purchasing decisions. Product quality shapes perceptions of value and satisfaction, while a strategic location facilitates access and attracts consumers, although limited access can be a constraint. This study aims to examine the influence of product quality and location, both partially and simultaneously, on purchasing decisions at CV Cita Mandiri.This research was a quantitative study involving two independent variables product quality and location and one dependent variable, purchasing decision. Data were collected through questionnaires distributed to 80 consumers of CV Cita Mandiri using purposive sampling. The data were analyzed using multiple linear regression to measure the effect of the two variables on purchasing decisions. The results showed that product quality had a significant effect on purchasing decisions. Location also had a significant influence. Simultaneously, both variables affected consumer purchasing decisions. However, other factors beyond product quality and location also contributed to purchasing decisions.The conclusion that can be drawn is that product quality and location play an important role in shaping consumers’ purchasing decisions at CV Cita Mandiri. The company is advised to maintain and improve product quality, including taste, durability, and packaging. In addition, improving location accessibility is necessary to make it easier for consumers to reach, for example by expanding the parking area or strengthening marketing through digital platforms to reach a wider market.